Bird diversity of tea plantations in Darjeeling Hills, Eastern Himalaya, India - ABHISHEK CHETTRI; KISHOR SHARMA; SAILENDRA DEWAN; BHOJ KUMAR ACHARYA (Biodiversitas Journal of Biological Diversity, 2018)
Chettri A, Sharma K, Dewan S, Acharya BK. 2018. Bird diversity of tea plantations in Darjeeling Hills, Eastern Himalaya, India. Biodiversitas 19: 1066-1073. The biodiversity wealth and conservation potential of agro-ecosystems including cash crop plantations is gaining significance in recent years. Agro-forestry provides ecosystem services similar to forest and, hence, support a high diversity of flora and fauna. This study was undertaken to explore the bird community in different tea gardens of Kurseong Hill, Darjeeling, Eastern Himalaya, India. Darjeeling is globally known for its extent and magnificent tea production. We sampled birds using point count methods along transects during August 2015-January 2016. A total of 581 individual birds comprising 48 species were recorded during the study. Amongst the guild types, insectivorous birds were the most dominant both in terms of species and abundances. Depending on their habitat preferences most of the birds were forest generalists followed by forest specialists. This study highlights that tea plantations have a great potential in harbouring and conserving birds and other associated life forms. Thus, proper management of these landscapes would be an effective strategy to conserve biodiversity of the Himalayas.